Electrical Design and Characterization of Plant Microbial Fuel Cell (PMFC) Using Water Hyacinth Plants with Variation of The Amount of Water and The Effect of Sunlight - pubiyanti, Intan; Suciyati, Sri Wahyu; Apriyanto, Donni Kis; Supriyanto, Amir (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Research on Plant Microbial Fuel Cells (PMFCs) has begun to develop, and various types of plants have been used. This research has realized PMFC using hyacinth plants by diversifying the amount of water and the effects of sunlight. The electrical properties of PMFCs aim to determine the effect of variations in the amount of hyacinth and sunlight on the power generated. In the reactor, the electrodes used are Cu and Zn plates. Data were collected by placing three reactors outdoors for 14 days or 331 hours. Based on the study's results, PMFC in reactor c, containing three clumps of hyacinth, obtained greater electrical power than in reactors A and b. The maximum electrical power is 6.31 mW on the 61st hour or 3rd-day measurement at 13.00 WIB. PMFC produces greater electrical power in external conditions than in internal conditions.